A Research on Ethnography of Communication: Ujuban in Tahlilan in Moslem Community in Tawang Village - Hasanah, Imroatul; Zen, Moch. Yusuf (Asketik: Jurnal Agama dan Perubahan Sosial, 2019)
This is qualitative research with the objective are to reveal the meanings behind Ujuban in Tahlilan and the factors involved in preserving Ujuban in Tahlilan in the Muslim community in Tawang village, Kediri Regency. This research is an ethnography of communication with Hymes’ SPEAKING model for analyzing the data. It was collected by observing, depth interviews, participating in group activities, and testing the validity of the data by using data triangulation. After five-month research, the result shows that Ujuban in Tahlilan has deep philosophical meanings as reflections of death. It also proves that factors of beliefs and socio-cultures bond the community to preserve Ujuban in Tahlilan which nowadays, is very rare. The research proves that religion even contributes to preserving the local culture descended from their ancestors, by embracing it in beautiful acculturation.